Open justice and the English criminal process - Simpson, Matthew (2008)
This thesis examines the concept of 'open justice' as it applies to the English criminal process. The conventional understanding of open justice requires merely that trial proceedings are open to the public and that those who attend are free to report to others what they have witnessed. This thesis seeks to demonstrate that the notion of open justice need not be so confined. The oversight of the criminal process provided by the courts, independent administrative bodies and the public, and the open manner in which such oversight is conducted, may be viewed as a more expansive conception of open justice. Such openness is argued to be required by the values of accountability, effective performance, rights protection, democracy and public confidence.